A Framework to Study Mixing Processes in the Marine Boundary Layer Using Water Vapor Isotope Measurements. Issue 5 (10th March 2018) - Benetti, M.; Lacour, J.‐L.; Sveinbjörnsdóttir, A. E.; Aloisi, G.; Reverdin, G.; Risi, C.; Peters, A. J.; Steen‐Larsen, H. C.
Abstract: We propose a framework using water vapor isotopes to study mixing processes in the marine boundary layer (MBL) during quiescent conditions, where we expect evaporation to contribute to the moisture budget. This framework complements the existing models, by taking into account the changing isotopic composition of the evaporation flux ( δ e ), both directly in response to the mixing and indirectly in response to mixing and surface conditions through variations in MBL humidity. The robustness of the model is demonstrated using measurements from the North Atlantic Ocean. This shows the importance of considering the δ e variability simultaneous to the mixing of the lower free troposphere to the MBL, to simulate the MBL water vapor, whereas a mixing model using a constant δ e fails to reproduce the data. The sensitivity of isotope observations to evaporation and shallow mixing further demonstrates how these observations can constrain uncertainties associated with these key processes for climate feedback predictions. Key Points: We developed a framework to evaluate how surface fluxes and shallow mixing affect the isotopic composition of the MBL vapor The validity of the model is demonstrated against observations representative of various oceanic conditions It complements the existing mixing models, which were not adapted to take into account the isotopic fractionation during evaporation